Rancang Bangun Sistem Informasi Assessment Risiko Tahanan berbasis Web Menggunakan Metode Rational Unified Process (Studi Kasus : Lembaga Pemasyarakatan Kelas IIB Selong) - anggin risna; Nadiyasari Agitha; Royana Afwani (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2021)
ABSTRACT Class IIB Correctional Institution of Selong is still using a manual system to assess a prisoner’s risk level resulting in a long process which is prone to error during the value input. It is also mandatory to recalculate the values to ensure the correct result is obtained. In this research, a website-based assessment system called “Website-Based Prisoner Risk Assessment Information System at Class IIB Selong Correctional Institution” is designed and built to help classify prisoners based on risk levels (low, medium, and high) which yields calculations results corresponding to the assessment guidelines. To support the website development, the object-oriented Rational Unified Process (RUP) software development method is deployed. Rational Unified Process (RUP) is chosen because it allows real-time explanation of the development process, has a clear system documentation, and flexible development process. The developed system is then tested using black-box testing and questionnaires. The black-box testing result is 1, which shows that all features in the system run correctly. Usability testing shows results at 89,7% which can be interpreted as “Very Good”, which infers that RUP is the right method for the system development.